Analysis of management support and self-efficacy on business sustainability through employee performance in micro and small businesses in Greater Jakarta - Djoko Setyo Widodo (Annals of Human Resource Management Research, 2025)
Purpose: The purpose of this study is to identify the factors that influence business sustainability, especially in micro and small businesses in Greater Jakarta. Methodology: The research employed a quantitative descriptive method using primary and secondary data. Primary data were collected through a 1–5 Likert scale questionnaire completed by employees of micro and small businesses in Greater Jakarta. Secondary data were sourced from relevant studies in reputable academic databases. The population size was unknown, and 131 respondents were selected using simple random sampling based on the Hair formula. Data were analyzed with SmartPLS 4.1.0.0 using outer model, inner model, and hypothesis testing. Results: The study on Micro and Small Enterprises in Jabodetabek reveals that management support and self-efficacy have positive and significant effects on employee performance and business sustainability. Employee performance also significantly influences business sustainability and plays a mediating role in strengthening the effects of management support and self-efficacy. These findings highlight the importance of managerial support and individual confidence in improving performance outcomes and ensuring sustainable business growth. Conclusions: The findings indicate that management support and self-efficacy significantly enhance employee performance and business sustainability in the land transportation sector. Employee performance serves as a key mediating factor that strengthens the impact of management support and self-efficacy on business sustainability. Limitations: This study is limited to examining the sustainability of micro and small businesses operating in the Greater Jakarta area, which may restrict the generalizability of the findings to other regions or business scales. Contribution: This study plays a role in identifying factors that influence the sustainability of micro and small businesses in Greater Jakarta, focusing on factors such as employee performance, management support, and self-efficacy.